Endodontic and periodontal management of a severely affected maxillary lateral incisor having combined mucosal fenestration and palatogingival groove - Sarang Sharma; Dhirendra Srivastava; Vishal Sood; Priya Yadav (Wolters Kluwer Medknow Publications, 2015)
Mucosal fenestrations, wherein the tooth root apices are clinically discernible in the oral cavity subsequent to loss of overlying alveolar bone and mucosa, are rare pathologic entities. Palato gingival grooves- anatomic aberrations are also infrequent occurrences that notoriously predispose to periodontal pathologies of varying extent. Both conditions independently are known to popularly affect maxillary lateral incisors. Coexistent fenestration defect and palato gingival groove in the same tooth is extremely rare and undoubtedly is a perfect combination to precipitate severe endodontic-periodontal consequences. In this report, a 34-year-old patient presented to the dental department with complaint of esthetics in relation to exposed root of right maxillary lateral incisor. On closer inspection, a palato gingival groove in addition to fenestration defect was evident on the root surface along with a periodontal pocket of >5 mm. An interdisciplinary treatment was instituted which included endodontic treatment followed by root end resection, osseous bone graft placement and guided tissue regeneration procedures for repair of mucosal fenestration defect. Debridement of the palatal pocket, with saucerization of the groove and restoration with glass ionomer cement were simultaneously employed to correct the palatal defect.